1986
DOI: 10.1159/000138218
|View full text |Cite
|
Sign up to set email alerts
|

Bay K 8644 and Acetylcholine: Different Interaction with Calcium Ions in the Rat Duodenal Muscle

Abstract: The contractile effect of the dihydropyridine analogue Bay K 8644, recently described as a Ca2+-agonist, has been evaluated in the rat isolated duodenal muscle in comparison with that of acetylcholine. Bay K 8644 (3 x 10–10–10–6 mol/l) increased the duodenal motility, whereas it behaved as an inhibitor when tested at high concentrations (>10–6 mol/l). Bay K 8644 was more potent than acetylcholine (threshold concentration 3 x 10–10 vs. 10–8 mol/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Experiments performed in Ca2+-free EGTA medium point out that the stimula tory action of Bay K 8644 is dependent on the extracellular calcium, as already sug gested [5,20], Furthermore, the persistence of stimulatory activity after simple removal of calcium from the nutrient fluid indicates an effect involving calcium pools not readily exchangeable with the extracellular fluids (tightly bound calcium) [3]. However, the residual tonic activity observed in the pres ence of EGTA does not exclude a parallel intracellular action [5].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Experiments performed in Ca2+-free EGTA medium point out that the stimula tory action of Bay K 8644 is dependent on the extracellular calcium, as already sug gested [5,20], Furthermore, the persistence of stimulatory activity after simple removal of calcium from the nutrient fluid indicates an effect involving calcium pools not readily exchangeable with the extracellular fluids (tightly bound calcium) [3]. However, the residual tonic activity observed in the pres ence of EGTA does not exclude a parallel intracellular action [5].…”
Section: Discussionsupporting
confidence: 61%
“…The marked decrease of the amplitude of spontaneous contractions observed at high concentrations of Bay K 8644 might be pos sibly related to the calcium antagonistic properties of the (+)-enantiomer already de scribed in other tissues [5,10]. However, an effect on inhibitory 'low-affinity' dihydropy ridine receptors cannot be excluded [7,20].…”
Section: Discussionmentioning
confidence: 84%
“…The nifedipine-resistant contractions were still cholinergic because they were abolished by atropine. In gastrointestinal systems, such as the mouse isolated distal colon, contractile activity induced by ACh is barely enhanced by Bay K 8644 and partially inhibited by nifedipine (Fontaine & Lebrun, 1988), and in rat duodenal smooth muscle the response induced by ACh is not modified by Bay K 8644 but can be significantly decreased by nifedipine (Coruzzi et al, 1986 1 fM its effect became negative. This characteristic of Bay K 8644 has been observed in many experiments (Bechem & Schramm, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…Earlier, it was reported [25] that GGA stimulates the mucus production by gastric mucosal cells, other studies [16, 17], however, have shown that the protective effect of GGA on the gastric mucosa is not abolished by NSAIDs which are known to inhibit the mucus production. Therefore, we believe that the most important mechanism by which GGA protects the gastric mucosa against NSAIDs is its potent induction of HSP70, based on the very recent findings by Tanaka et al [26] who clearly demonstrated that GGA does not protect the gastric mucosa against NSAIDs in heat shock factor 1-null mice.…”
Section: Discussionmentioning
confidence: 99%